Medical rehabilitation after lower limb injuries in patients with diabetes mellitus: a review - Valeriia A. Vasileva; Larisa A. Marchenkova; Daria I. Otvetchikova; Elena A. Rozhkova; Anatoliy D. Fesyun (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. Diabetes mellitus (DM) in patients with lower extremity injuries is a global health problem. The combination of these pathologies in one patient requires rehabilitation measures to restore maximum functional activity and maintain the patients' initial quality of life. Diabetes as an independent pathology has a negative impact on the patient's health and also aggravates the recovery period after traumatic bone injury, increasing the risk of adverse outcomes in the early and late postoperative periods. AIM. To analyze the scientific data of the last ten years on the use of medical rehabilitation methods in patients with lower extremity injuries and diabetes mellitus. MAIN CONTENT. The search was conducted in Web of Science, PubMed, and Scopus according to PRISMA guidelines and initially identified 181 records. Of these, 45 articles were included in the study with publication periods 2013-2023. Key words used: lower limb injuries, diabetes mellitus, rehabilitation, mechanotherapy, physical therapy, physiotherapy. The literature review analyzes publications on the basis of which a description is made that in case of injuries of the lower extremities in patients with diabetes, the participation of specialists from a multidisciplinary team is necessary to draw up an optimal rehabilitation program aimed at preventing the occurrence of complications and their progression, achieving a speedy and complete recovery of lost functions. A personalized approach, individually selected therapy methods and the use of modern technologies will help achieve the best results in the recovery of patients with diabetes and lower extremity injuries. CONCLUSION. The review formulated a conclusion about the main objectives of rehabilitation: which include: control of glucose levels and metabolic disorders; examination and care of damaged tissues in order to prevent the development of ulcers and infection of injured skin; gradual increase in physical activity; goals should take into account the individual characteristics of the patient; the use of physiotherapy methods to improve microcirculation and activate tissue regeneration (transcutaneous electrical nerve stimulation (TENS), electrophoresis, magnetic fields, ultratonotherapy, cryotherapy, laser therapy, darsonvalization, pulsed electric fields, ultrasound therapy, ozokerite therapy and peloid therapy); the use of mechanotherapy with biofeedback and robotic systems to increase overall endurance, strength, improve balance function and form the correct walking stereotype (rehabilitation track with visual feedback about walking C-Mill).